The reflection on theater education – the need and the meaning - Szewczyk-Kowalewska, Irena; Kowalewski, Michał (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
The study aimed at popularizing the need and importance of theater education in the in the children and youths’ education. The concept of sustainable education through art, including theater education to raise public awareness, should be at least on par with the need to carry out preventive examinations. All treatments aimed at the development and improvement of human contribute to the progress of civilization have a bearing on the emotional, moral, ethical and intellectual aspects of the society.The article is an attempt to synthesize theoretical literature on the subject supported by the results of measurable learning experiences in schools and other cultural centers. Modern education should develop creative students’ attitudes. The role of the educator is not only shaping the axiological system, but also stimulating creative activity among his wards.